2018
DOI: 10.3389/fneur.2018.01044
|View full text |Cite
|
Sign up to set email alerts
|

Postural Dynamics Are Associated With Cognitive Decline in Parkinson's Disease

Abstract: Early features of Parkinson's disease (PD) include both motor and cognitive changes, suggesting shared common pathways. A common motor dysfunction is postural instability, a known predictor of falls, which have a major impact on quality of life. Understanding mechanisms of postural dynamics in PD and specifically how they relate to cognitive changes is essential for developing effective interventions. The aims of this study were to examine the changes that occur in postural metrics over time and explore the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
5
32
0
Order By: Relevance
“…As PD progresses, non-dopaminergic motor circuits are also involved, exacerbating the axial motor features that do not usually respond to standard antiparkinsonian medication [3,4]. Gradual deterioration of muscle strength, balance, and gait, causes postural instability and immobility [5], which considerably diminish quality of life, and are known as risk factors for fall [6,7]. Several studies suggested rehabilitation as an adjuvant to pharmacological and surgical treatments [1,8], which is proven to slow down the progression of PD and act as a neuroprotective strategy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As PD progresses, non-dopaminergic motor circuits are also involved, exacerbating the axial motor features that do not usually respond to standard antiparkinsonian medication [3,4]. Gradual deterioration of muscle strength, balance, and gait, causes postural instability and immobility [5], which considerably diminish quality of life, and are known as risk factors for fall [6,7]. Several studies suggested rehabilitation as an adjuvant to pharmacological and surgical treatments [1,8], which is proven to slow down the progression of PD and act as a neuroprotective strategy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Multipoint-assessment design is generally used to evaluate the follow-up lasting effects of an applied surgical [3] or physical [6,27] therapy, or to investigate the natural progression of L-dopa treated PD [2,7]. To the best of our knowledge, there is no study which investigated the learning dynamics in postural control during a balance-training program.…”
Section: Introductionmentioning
confidence: 99%
“…Jerk RMS is a measure of the amplitude of the rate of change in acceleration, allowing for the measurement of the "constraint" of movement during the YBT reach excursions by quantifying the smoothness of the movement. 25,26 The mean of the three maximal reach attempts in each reach direction was obtained for each variable (normalized reach distance; Gyro SEn; Jerk RMS), to ensure measurement reliability. The signal processing and data analysis was conducted using MATLAB (2018b, MathWorks, Natwick).…”
Section: Signal Processing and Data Analysismentioning
confidence: 99%
“…The majority of RCTs are designed with assessments at baseline and follow-up after intervention; and only a few used intermediate assessments during a training program [24][25][26]. Multipoint-assessment design is generally used to evaluate the follow-up lasting effects of an applied surgical [3] or physical [6,27] therapy, or to investigate the natural progression of L-dopa treated PD [2,7]. To the best of our knowledge, there is no study which investigated the learning dynamics in postural control during a balance-training program.…”
Section: Introductionmentioning
confidence: 99%